(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Excavation of the ‘monumental complex’ of the Civita of Tarquinia yielded structures excavated in the rock in the north-western sector (sector N). Their recurring features are: connection to artificial structures, sealing marking them out of adjacent layers, presence of small white stones unrelated to the geological reality of the plateau. Such recurrences make it possible to figure out the existence of specific rituals focused on the particular choice of this type of rock and connected to the surrounding structures.